Seismic Microzonation For Banda Aceh City – A GIS Approach - Adi Safyan; Fouziah Johar; M. Rafee Majid; Deassy Siska (Faculty of Engineering, Malikussaleh University, 2018)
Banda Aceh which lies about 100 km from Sumatra Subduction Zone and 10 km close to the Sumatran Transform Faults makes this place extremely vulnerable to earthquake hazards. Learning from the earthquake and tsunami on December 26 th 2004 which caused many deaths, property loss and devastation of the city, urban planning and development in the future should consider these earthquake potential hazards. Based on this purpose, seismic microzonation maps which identify and map different earthquake hazard potentials can be used as reference or tool in the initial phase of earthquake risk mitigation. The main objective of this study is how to create seismic microzonation maps using Geographic Information Systems (GIS) and in turn can be used as guidance in urban planning and development. The maps incorporate various seismic hazard maps including ground shaking hazard map, liquefaction hazard map, landslide hazard map, surface faulting hazard map and tsunami hazard map.KEY WORDS: Earthquake, Hazard, Seismic Microzonation, GIS.